Correlational Study of Breast Cancer with Age, Marital and Socio-Economic Status in Women Using Clinical Data from Selected Hospitals in Southern Nigeria - Kennedy Irikefe Ekerikevwe; Anthony K. Odior (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Cancer, also called malignancy, is an abnormal growth of cells. There are more than 100 types of cancer, including breast cancer, skin cancer, lung cancer, colon cancer, prostate cancer, and lymphoma. The morbidity of breast cancer has eaten up lots of women in the society today. This study, therefore, attempts to examine the relationship between the clinical episodes of breast cancer with age, marital and socio-economic status in women using data from selected hospitals in southern Nigeria. Reviews of medical records of 100 women with breast cancer from four randomly selected public hospitals in the southern part of Nigeria were made. The clinical episode of breast cancer of the 100 patients in the four hospitals were observed and documented for statistical analysis. The data collected include the bio-data, age, marital and socio-economic status of patients with breast cancer. The results of the Pearson’s correlation show that breast cancer is highly correlated with marital status, positively related with the present age of attack, negatively correlated with age at first birth and negatively correlated with women socio-economic status. The result collaborates a previous study made by Halabi and Bondy (2014). The study concluded that age and marital status are major risk factors of incidence of breast cancer among women in southern Nigeria. The study therefore recommends that there should be a better focused health education, marriage before sex orientation and other preventive strategies for Nigerian women and that the National Health Insurance Scheme (NHIS), should as a matter of urgency, incorporates women with breast malignancy into the scheme for adequate care, palliatives and stimulus. There should be adequate awareness about the disease and access to health care facilities for women in southern Nigeria to carry out routine check for lumps in their breast.